West Java Cultural Park as an Upcoming Cultural Tourism Asset - Syahra Sabina; Marsya Listianty (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2024)
The West Java Cultural Park has become a significant focus in the development of cultural tourism in the region. This research aims to analyze the roles of the West Java Cultural Park as a future cultural tourism assets . The research method involves surveys and data analysis to understand the perceptions of local communities and tourists towards the cultural park . Findings indicate that the West Java Cultural Park has been great potential as a cultural tourism attractions with its unique artistic and cultural richness . The implication is the need for greater preservation and promotion efforts to increase tourists visits and raises awareness of the importance of West Java's cultural heritage .